GAYA KEPEMIMPINAN GURU AGAMA HINDU BERBASIS KOMUNIKASI INTERAKTIF DALAM PEMBELAJARAN DI TK BINA PUTRA CANDIKUNING - I Made Yoga Mahendra; I Nengah Lestawi; I Gede Suwindia (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2021)
Children have different characters and developments. This study aims to find out why the learning process at Bina Putra Candikuning Kindergarten is not going well, then how is the leadership style of Hindu religious teachers based on interactive communication in Bina Putra Candikuning Kindergarten in learning and the implications of the leadership style of Hindu religious teachers based on interactive communication. This research is a descriptive qualitative research. The research subjects were Hindu religious teachers at TK Bina Putra Candikuning. This study uses methods for data collection in the form of observation, interviews, documentation, and literature study. The results showed that educational management at Bina Putra Candikuning Kindergarten experienced obstacles faced by Hindu religious teachers in implementing an interactive communication-based leadership style. There are several obstacles experienced, namely the communication of teachers, students and the ability to use media. The leadership style of Hindu religious teachers based on interactive communication in learning at TK Bina Putra Candikuning is a democratic leader style. The leadership style of Hindu religious teachers at Bina Putra Kindergarten is implemented in the learning of discipline and harmony. The implications of the leadership style of the Hindu religious teacher based on interactive communication in learning at Bina Putra Candikuning Kindergarten are the implementation of interactive communication in learning, the formation of teacher and student communication through the media, and the achievement of student achievement.